2021
DOI: 10.22167/2675-441x-20210573
|View full text |Cite
|
Sign up to set email alerts
|

Effect of galectin-1 administration on pregnancy rate and its economic viability in TAI procedures in beef cattle

Abstract: The purpose of this work is to demonstrate the reproductive efficacy and the economic impact of a complementary tool to the TAI (timed artificial insemination) protocols - the administration of a single dose of recombinant human galectin-1 (rHGAL1) during the insemination procedure. GAL-1 can be considered as a modulator of the pregnancy development process. Reproductive efficacy was verified through the pregnancy rate in the first service, by ultrasonography (at 28-35 days) in contemporary groups (YG) of cows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 36 publications
(53 reference statements)
0
9
0
1
Order By: Relevance
“…There are so many particularities between placentation and embryo elongation of different mammals' species but, based on [20,21,22], that described that GAL-1 has a high degree of structural conservation, dimerization, and binding properties with carbohydrates and integrins (adhesion proteins), suggesting that these properties are conserved among vertebrates and that they maintain a pattern of gene expression among the different types of the placenta (deciduous or not), supported the decision to use a human gene to produce the recombinant protein for other species. Previous studies have demonstrated the biological functionality of rHGAL-1 to improve the pregnancy rate in cows, suggesting the potential use in other species [1,2].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are so many particularities between placentation and embryo elongation of different mammals' species but, based on [20,21,22], that described that GAL-1 has a high degree of structural conservation, dimerization, and binding properties with carbohydrates and integrins (adhesion proteins), suggesting that these properties are conserved among vertebrates and that they maintain a pattern of gene expression among the different types of the placenta (deciduous or not), supported the decision to use a human gene to produce the recombinant protein for other species. Previous studies have demonstrated the biological functionality of rHGAL-1 to improve the pregnancy rate in cows, suggesting the potential use in other species [1,2].…”
Section: Discussionmentioning
confidence: 99%
“…The method for obtaining rHGAL -1 is determined by the manufacturing process of Inprenha Biotecnologia® and is previously wholly described [1,2]. Aliquots of E. coli strains transformed with the vector insertion containing the GAL-1 gene (pET-29a(+)+lgals-1 gene 1 ) were grown in systems with LB Broth Base medium containing kanamycin sulfate until obtaining optimal bacterial growth rate, demonstrated by optical density.…”
Section: Rhgal-1 Production and Purification -mentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction between GAL-1 and integrins suggested participation at extracellular matrix and placentation events, like in the oxygen and/or nutrients exchanges or angiogenesis events (vessels formation). It can be elucidated that GAL-1 plays a vital role in maternal-fetal interface signaling since it has multiple biological functions [9,29]. Blois et al (2007) [25] demonstrated high pregnancy loss rates in mice in which the Lgals1 gene was deficient (knockout mice).…”
Section: Why Could Galectin-1 Improve the Pregnancy Rate?mentioning
confidence: 99%
“…Thus, when used correctly, the results are promising. In cattle, a single eGAL-1 intrauterine dose is indicated as a health catalyst of animal fertility, it being, therefore, a tool to increase the reproductive/productive efficacy and the economic profitability using the eGAL-1 was discussed by Roncoletta et al (2021) [29]. The approach can be different in humans and endangered mammals, not for economic appeal, but as an alternative method to aid in the exhausting process of helping some couples achieve pregnancy.…”
Section: Why Could Galectin-1 Improve the Pregnancy Rate?mentioning
confidence: 99%